Minat Mahasiswa Menggunakan Halodoc Selama Pandemi Covid-19 - Nauri Anggita Temesvari; Angelia Dyah Sukmarini; Melani Nurbaiti Hasanah (Indonesian of Health Information Management Journal (INOHIM), 2023)
AbstractTechnology was widely used by people during the COVID-19 period, including searching for health-related information. Halodoc's presence at this time was a technological breakthrough that provided various features useful in pursuing public health, among other applications. The pandemic has made students must be familiar with technology in online learning systems. However, students did not optimally use the technology for health-related during the pandemic. This study aimed to assess the relationship between students' perceptions of security, trust, ease of use, and usefulness with interest in using Halodoc during the COVID-19 pandemic. This study used a cross-sectional design, and the data was collected using Google Forms. The number of samples obtained was 100 students. The chi-square test was used to find the relationship between perceptions of security, trust, ease of use, and usability with interest in Halodoc during the COVID-19 pandemic. Among 100 students, 93% stated interest in using Halodoc, 83% stated Halodoc was very safe, 87% stated they believed Halodoc, 90% stated Halodoc was easy to use, and 91% said Halodoc was useful. Perceptions of trust (p-value 0.005) and usefulness (p-value 0.015) were significantly related to students' interest in using Halodoc during the COVID-19 pandemic. Perceptions of security (p-value 0.340) and convenience (p-value 0.144) were not significantly related to students' interest in using Halodoc during the pandemic. Perceptions related to trust and usefulness were factors that determined students' interest in using Halodoc during the pandemic.Keyword: Halodoc, interests, students, technology, COVID-19 AbstrakPenggunaan teknologi semakin pesat selama COVID-19 dalam berbagai hal termasuk dalam pencarian informasi terkait kesehatan. Halodoc hadir sebagai teknologi dengan berbagai fitur yang dapat berguna dalam pencarian kesehatan bagi masyarakat diantara aplikasi lainnya pada masa pandemi. Teknologi pada periode ini secara intensif digunakan mahasiswa dalam pembelajaran dengan sistem e-learning. Namun penggunaan aplikasi kesehatan belum optimal digunakan mahasiswa selama pandemi COVID-19. Penelitian ini menilai hubungan antara persepsi mahasiswa tentang keamanan, kepercayaan, kemudahan penggunaan, dan kebermanfaatan dengan minat menggunakan Halodoc selama pandemi COVID-19. Desain potong lintang digunakan dalam penelitian. Jumlah sampel didapatkan 100 mahasiswa. Uji chi-square digunakan untuk menguji keterkaitan persepsi keamanan, kepercayaan, kemudahan penggunaan, dan kebermanfaatan dengan minat menggunakan Halodoc selama pandemi COVID-19. Dari 100 mahasiswa, 93% menyatakan minat dalam menggunakan Halodoc, 83% menyatakan Halodoc sangat aman, 87% menyatakan percaya dengan Halodoc, 90% menyatakan Halodoc mudah digunakan, dan 91% menyatakan Halodoc bermanfaat. Persepsi kepercayaan (p-value 0,005) serta kebermanfaatan (p-value 0,015) signifikan terkait dengan minat mahasiswa menggunakan Halodoc selama pandemi COVID-19. Persepsi persepsi keamanan (p-value 0,340) dan kemudahan (p-value 0,144) tidak signifikan terkait dengan minat mahasiswa menggunakan Halodoc selama pandemi COVID-19. Persepsi terkait kepercayaan dan kebermanfaatan menjadi faktor yang menentukan minat mahasiswa menggunakan Halodoc selama periode COVID-19.Kata Kunci: Halodoc, minat, mahasiswa, teknologi, COVID-19